Synthesis of 6-isopropoxy-2-phenyl-4,4a,6,8a-tetrahydropyrano[3,2-d][1,3]dioxine via Palladium catalysed O- Glycosylation (Indian Journal of Chemistry (IJC), 2025)
One of the important and known processes in the chemistry of carbohydrates is the glycosylation reaction, in which C–O bonds are commonly used to join two different units. One of the most difficult but crucial aspects of glycochemistry to be addressed in the quest to advance this field is the design and development of sustainable catalytic methods for O-glycosylation. Here, we describe a straightforward and effective O-glycosylation technique using palladium as a catalyst, which involves triggering the activity of a phenylpropiolate glycoside donor.